Feed additives for methane mitigation: Recommendations for identification and selection of bioactive compounds to develop antimethanogenic feed additives - Zoey Durmic; Evert C. Duin; André Bannink; Alejandro Belanche; Vincenzo Carbone; M. Dolores Carro; Max Crüsemann; Veerle Fievez; Florencia Garcia; Alex Hristov; Miroslav Joch; Gonzalo Martinez-Fernandez; et al. (Journal of Dairy Science)
ABSTRACT: Despite the increasing interest in developing antimethanogenic additives to reduce enteric methane (CH4) emissions and the extensive research conducted over the last decades, the global livestock industry has a very limited number of antimethanogenic feed additives (AMFA) available that can deliver substantial reduction, and they have generally not reached the market yet. This work provides technical recommendations and guidelines for conducting tests intended to screen the potential to reduce, directly or indirectly, enteric CH4 of compounds before they can be further assessed in in vivo conditions. The steps involved in this work cover the discovery, isolation, and identification of compounds capable of affecting CH4 production by rumen microbes, followed by in vitro laboratory testing of potential candidates. The finding of new bioactive compounds as AMFA can be based on 2 approaches: empirical and mechanistic. The empirical approach involves obtaining and screening compounds present in databases and repositories that potentially possess the desired effect but have not yet been tested, screening natural sources of secondary compounds such as plants, fungi, and algae for their antimethanogenic effects, or examining compounds with antimethanogenic effect on microbes in other research domains outside the rumen. In contrast, the mechanistic approach is the theoretical process of discovery new bioactive compounds based on existing knowledge of a biological target or process. The in vitro methodologies reviewed include examining effects at the subcellular level, in single pure cultures of methanogens and examining in more complex mixed rumen microbial populations. Simple in vitro methodologies (subcellular assessments and batch culture) allow testing a large number of compounds, whereas more complex systems simulating the rumen microbial ecosystem can test a limited number of candidates but provide better insight about the antimethanogenic efficacy. This work collated the main advantages, limitations, and technical recommendations associated with each step and methodology use during the identification and screening of AMFA candidates.